Evaluation of the Clinical and Immunological Parameters During Treatment Chronic Periodontitis by Camelyn Mouthwash - Kachkachishvili, Irma; Korsantia, Boris; Bakradze, Mzia; Aladashvili, Lali; Taboridze, Iamze (European Scientific Journal, ESJ, 2017)
The purpose of study is Evaluation of Clinical and Immunological effects of using Camelyn in Periodontology. Materials and methods: We have studied clinical and immunological features of 20 patients with periodontitis between ages 20 and 60 (these patients were from the dental clinic Mitra). CPI index has been studied dynamically — before treatment, after treatment, 6 months and 1 year later. Treatment included scaling and root planning. During these 2 weeks we have used 10 ml of Camelyn 25 percent solution for rinsing. We applied it for 2 minutes. We checked cellular and humoral immunity in peripheral blood stem. Lysozyme activation was determined. Results: After treatment, the median CPI index was significantly reduced. After 6 months and a year of treatment it was insignificantly increased, but in comparison with the initial CPI it was remained significantly less.Before starting treatment Interferon and the phagocytic system was significantly lowered, also amount of TLymphocytes, but the amount of T suppressors was increased; After the treatment mentioned above the parameters were significantly increased, although in comparison with the standard it still was low. After the treatment the amount of T- suppressors was significantly decreased.Saliva significantly showed a reduction of the amount of lysozyme and sIgA Before treatment IgG was significantly lower and IgM higher. After the treatment all kinds of Immunoglobulins were almost the same; Conclusion: Including Camelyn in traditional treatment of periodontitis promotes immune response activation and it has a positive influence on a clinical picture —it improves periodontitis clinical features and significantly reduces CPI index.